2022
DOI: 10.1186/s12887-022-03262-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating innate lymphoid cell (ILC)1 and decreased circulating ILC3 are involved in the pathogenesis of Henoch-Schonlein purpura

Abstract: Background Innate lymphoid cell (ILC) dysfunction is involved in numerous immune diseases, but this has not been demonstrated in Henoch-Schonlein purpura (HSP). This study aimed to investigate whether ILC dysfunction or imbalance participate in the pathogenesis of HSP. Methods This was a prospective study in patients with HSP who were hospitalized at the Children’s Hospital of Soochow University from June to December 2019. Age- and sex-matched cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Yeast is able to colonize the mouse intestine and become the predominant species further reshaping the microbiota and intestinal microenvironment (Dong et al, 2022 ). The functional prediction of gut microbiota demonstrated a reduced Th17 cell/IL17 signaling pathway in the yeast vaccine group, which also decreased the intestinal inflammation response (Zhang et al, 2022a ). Taken together, these results indicated that oral administration of yeast vaccine might facilitate the repairmen of gut mucosa damage caused by pathogen invasion, which elicit the innate intestinal mucosal immunity to protect the organism from fatal influenza virus infection (Ravindran and Thornton, 2022 ; Serafini et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast is able to colonize the mouse intestine and become the predominant species further reshaping the microbiota and intestinal microenvironment (Dong et al, 2022 ). The functional prediction of gut microbiota demonstrated a reduced Th17 cell/IL17 signaling pathway in the yeast vaccine group, which also decreased the intestinal inflammation response (Zhang et al, 2022a ). Taken together, these results indicated that oral administration of yeast vaccine might facilitate the repairmen of gut mucosa damage caused by pathogen invasion, which elicit the innate intestinal mucosal immunity to protect the organism from fatal influenza virus infection (Ravindran and Thornton, 2022 ; Serafini et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%